REFORMS IN THE REPUBLIC OF UZBEKISTAN IN IMPROVING THE QUALITY OF EDUCATION AND THE ISSUE OF PERSONNEL (IN THE EXAMPLE OF HIGHER EDUCATION INSTITUTIONS) (American Journal of Research in Humanities and Social Sciences, 2023)
This article talks about the reforms and personnel issue in the Republic of Uzbekistan to improve the quality of education. Based on historical data, the author studied and analyzed the specific aspects of the reforms and personnel issue in the Republic of Uzbekistan to improve the quality of education on the basis of existing scientific literature.